Frequency of depression and risk factors associated with students from first to eight semester in a decanate of UCLA, january-may 2013 (Revista Venezolana de Salud Pública, 2018)
Depression occupies one of the first places as a reason for consultation in psychiatry, with university students being one of the groups most affected. The objective of this investigation was to determine the frequency of depression and associated risk factors in students from the first to the eighth semester in a UCLA Deanery January-May 2013. A cross-sectional, observational analytical study was carried out, In 230 students, 149 females and 81 males. Data collection included a self-administered questionnaire for the measurement of risk factors, validated by experts, and the Beck Depression Inventory of 21 items. It was evidenced that there are 22.6% of depressed students, of whom 20.0% correspond to mild depression and 2.6% to moderate depression. There was a higher frequency of depression in the female sex (25.3%); In students over 20 years old (24.2%); In foreigners (28.1%); In students from the III and VII semesters (29.4% and 34.8%, respectively). In students with regular academic performance, 36.2% (p = 0.0001) of depression was observed; In those who do not share quality time with their family, 50% were evidenced (p = 0.0000); 44.4% (p = 0.000) and 50% (p = 0.007), respectively. Likewise, there is a 35.7% depression rate in students who have poor teacher-student relationships (p = 0.0007), with no respect (p = 0.021) and equity (p = 0.003). Likewise, 28.9% of students with depression have a poor relationship with their classmates. In conclusion, there is a significant percentage of depressed students, mild depression prevailing in them, however, non-depressed students present some risk factors. This paper aims to serve as a pioneer in the aforementioned campus for other research since there is little information on the subject
Keywords: Venezuela; Depression; university